Antibacterial activity of a new monocarbonyl analog of curcumin MAC 4 is associated with divisome disruption - Polaquini, Carlos R. [UNESP]; Marques, Beatriz C. [UNESP]; Ayusso, Gabriela M. [UNESP]; Morão, Luana G. [UNESP]; Sardi, Janaína C.O.; Campos, Débora L. [UNESP]; Silva, Isabel C. [UNESP]; Cavalca, Lúcia B. [UNESP]; Scheffers, Dirk-Jan; Rosalen, Pedro L.; Pavan, Fernando R. [UNESP]; Ferreira, Henrique [UNESP]; et al. (Elsevier, 2021)
Curcumin (CUR) is a symmetrical dicarbonyl compound with antibacterial activity. On the other hand, pharmacokinetic and chemical stability limitations hinder its therapeutic application. Monocarbonyl analogs of curcumin (MACs) have been shown to overcome these barriers. We synthesized and investigated the antibacterial activity of a series of unsymmetrical MACs derived from acetone against Mycobacterium tuberculosis and Gram-negative and Gram-positive species. Phenolic MACs 4, 6 and 8 showed a broad spectrum and potent activity, mainly against M. tuberculosis, Acinetobacter baumannii and methicillin-resistant Staphylococcus aureus (MRSA), with MIC (minimum inhibitory concentration) values ranging from 0.9 to 15.6 µg/mL. The investigation regarding toxicity on human lung cells (MRC-5 and A549 lines) revealed MAC 4 was more selective than MACs 6 and 8, with SI (selectivity index) values ranging from 5.4 to 15.6. In addition, MAC 4 did not demonstrate genotoxic effects on A549 cells and it was more stable than CUR in phosphate buffer (pH 7.4) for 24 h at 37 °C. Fluorescence and phase contrast microscopies indicated that MAC 4 has the ability to disrupt the divisome of Bacillus subtilis without damaging its cytoplasmic membrane. However, biochemical investigations demonstrated that MAC 4 did not affect the GTPase activity of B. subtilis FtsZ, which is the main constituent of the bacterial divisome. These results corroborated that MAC 4 is a promising antitubercular and antibacterial agent.
Keywords: Antibacterial; Antitubercular; Bacterial division; Curcumin; Membrane; Monocarbonyl; Phenol